Subjetividades e negritudes: relações raciais, racismo e invenção da existência - Barrozo, Helom de Oliveira (2019)
This dissertation analyses the modes of subjectivation present in the African and Afrodiasporic peoples, combining the ways in which these experiences and knowledge contribute to think about the present and hegemonic subjectivities, that is, which advances are possible deriving out of the African perspective. In order to do so, the routes of oral tradition, of gender relations, of community experience and of ways of caring and of health production were used. At first, the concept of subjectivity and racism as a mode of production are discussed, inserting the notion of identity and the respective consequences for racial relations, asserting the need to affirm multiplicity, singularity and the common as ways of fighting against racism. From that moment on, the African presence is strengthened, comprehending the importance of the word and its respective powers of transformation of reality, constituting peace or war; the constitutive processes; the holistic perspective and modes of relation with the environment, with ancestry and with those who have not yet been born; paradigm of health care; the universal as an aspect of the pluriverse, the affirmation of the multiplicity of centers; the strengthening of community experience, shifting the understanding of individualism as opposed to collectivity and betting on the radicality of groupality as an outlet for social problems and the affirmation of social welfare.